Pengembangan Video Broadcasting Server Untuk Live Streaming Menggunakan Nginx dan RTMP Dengan Studi Kasus Teleconference - Tommy Andreas Susanto; Henry Novianus Palit; Agustinus Noertjahyana (Jurnal Infra, 2017)
Globalization Era has pushed the communication around the world to be more intensive. The communication that has been provided by technology can even be used real time. Globalization also pushed the cooperation of universities or institution between countries, Communication is needed to establish cooperation, and teleconference is the best method of communication to establish this cooperation. Nginx and RTMP is used to develop this broadcast server, the server can be used for live streaming both publicly and privately, via self-owned hardware and network, so the usage of existing platform can be negated. Users are able to use the server for teleconference and other real-time communication activities. Server can also archive the live streaming session, and the file from archive can be played on demand. The server can also become a relay to transmit a stream that its currently receiving to another platform or other server. After a series of test, server is able to use the features than had been worked on, and can be used as self-hosted server for live streaming, especially teleconference.